Stock market integration and international portfolio diversification : a study of the Asian financial crisis (1996–2007) / Surianor binti Kamaralzaman - Kamaralzaman, Surianor (2015)
The purpose of this thesis is to investigate a comprehensive, concurrent comparison of the linkages and the potential benefits of international diversification between Malaysian financial market and developed and developing countries. This study takes a two-fold approach to investigate the issue of market integration. First, the short and long run co-movements with the Malaysian market of twenty-one of the most developed and developing equity markets in the world are examined by employing econometric methodology and utilizing standard cointegration analysis. Second, mean variance analysis and the construction of a portfolio are employed to form efficient frontiers. This study is divided into four sub periods to capture the effects on the Malaysian market of various stages. In addition, daily closing MSCI indices are used and the influence of the financial crisis are also analyzed by contrasting different periods from 1996-2007. The findings suggest that, between the Malaysian and developed markets, there were long-run relations during during the pre-crisis and post crisis period, which indicates that there is contagion effect and that obtaining abnormal profits through portfolio diversification is limited in the long-run. However, there are substantial short-run dynamic interactions between the developed and the Malaysian market for all sub periods. Moreover, the results suggest that long-run relationships among all the markets under consideration were altered by the crisis and were actually strengthened. There is less bidirectional relationships between the developed markets and the Malaysian markes during the pre-crisis and crisis period as compared to the post crisis period. Furthermore, the developed countries (larger economies) are higher degree Granger cause developing (smaller economies) countries. Between the Malaysian and developing markets, one general conclusion that can be drawn from this long run relationship is that the developing stock markets were moving towards a greater integration either among themselves or with the Malaysian market during the crisis period and were weakened after the crisis. Findings further imply that there was room to gain benefit from the international investment diversification to be earned by investors across developing stock markets in the post financial crisis period as the markets tended to be weaker. There appear to be extensive short-run dynamic interactions between the developing and Malaysian markets in the short-run. Furthermore, the investment proportion of optimal portfolios for various interest rates between Malaysia with the developed and developing markets under consideration are different for all sub periods. In addition, it can be clearly seen that the efficient frontiers of the Malaysian and developing countries for the pre crisis and post crisis are generally superior to those for during the overall period and crisis period. An important implication of the findings is that the degree of integration among developed and developing countries tends to change over time, especially around periods marked by financial crisis. Furthermore, for policymaking, any disturbances in the markets of the US, Japan, Hong Kong or India should be taken into consideration by the Malaysian authorities in designing policies that have repercussions on the Malaysian market.